Physical and mechanical properties of thin paper sheets made from onion peels (Allium cepa) / Mohammad Harris M. Yahya, Normala Hassim and Mohd Rozi Ahmad - M. Yahya, Mohammad Harris; Hassim, Normala; Ahmad, Mohd Rozi (Universiti Teknologi MARA, Negeri Sembilan, 2020)
The present work deals with the production of paper materials from onion peels (Allium Cepa) fibers as an alternative potential non-wood fiber. The onion peels were obtained from a local small and medium food industry. The onion peels were cooked at 120, 150 and 180 minutes. The peels were grinded and poured in a set of mould and deckle for the formation of a thin sheet of paper. The physical, mechanical, morphological characteristics and water rise capillary values (KLEMM Method) were evaluated to determine its suitability for a paper material. The results show that the increase in cooking time from 120 to 180 minutes resulted in an increase in the tensile index from 32.28N*m/g to 42.13N*m/g and tear index from 9.80mN*m2/g to 15.62mN*m2/g. The bonding strength increased due to higher number of fibers, finer fiber size, and increase in the fiber contact area and fiber distribution. The high porosity area affects the performance of water rise capillary values of the paper sheets. The onion peels fiber gave impressive handsheets characteristics when compared with other sources of non-wood fibers.